3D printing of sensors, actuators, and antennas for low-cost product manufacturing - Singh, Rupinder (Sustainable manufacturing technologies, 2023)
This book discusses the 3D printing of sensors, actuators, and antennas and illustrates how manufacturers can create smart materials that can be effectively used to prepare low-cost products. The book also includes how to select the appropriate process for your manufacturing needs. 3D Printing of Sensors, Actuators, and Antennas for Low-Cost Product Manufacturing offers the most recent developments in 3D printing of sensors, actuators, and antennas for low-cost product manufacturing; the book highlights some of the commercially available low-cost 3D printing processes that have higher efficiency and accuracy. Fundamental principles and working methodologies are presented with a critical review of the past work involved and current trends with future predictions. It covers composite and polymeric materials widely used and specifically focuses on low-cost elements. Recent breakthroughs and advantages in product manufacturing when printing smart materials are also discussed. Manufacturing engineers, product designers, manufacturing industries, as well as graduate students, and research scholars will find this book very useful for their work and studies